Study of the polyacrylate interpenetration in a collagen-polyurethane matrix to prepare novel hydrogels for biomedical applications - Claudio-Rizo, Jesús A.; González-Lara, Irving A.; Flores-Guía, Tirso E.; Cano-Salazar, Lucía F.; Cabrera-Munguía, Denis A.; Becerra-Rodríguez, Juan J. (International journal of biological macromolecules, 2020)
Currently, the control of the properties of collagen based hydrogels represents a promising area of research to develop novel materials for biomedical applications. The crosslinking of the collagen with trifunctional polyurethane (PU) allows a hybrid matrix to be formed by improving the coupling with exogenous polymeric chains to generate innovative semi-interpenetrated network (semi-IPN) hydrogels. The incorporation of polyacrylate (PA) within a hybrid matrix of collagen-PU allows to regulate the structure and physicochemical properties such as polymerization rate, physicochemical crosslinking, thermal stability, storage module and swelling/degradation behavior of the 3D matrices in the hydrogel state, also exhibiting modulation of their in vitro biocompatibility properties. This work contemplates the study of the effect of PA concentration on the physicochemical properties and the in vitro biological response of these novel semi-IPN hydrogels based on collagen-PU-PA. The results indicate that semi-IPN hydrogels that include 20 wt% of PA exhibit improved swelling with respect to the collagen-PU hydrogel, controlling the degradation rate in acidic, alkaline and proteolytic media; showing E. coli inhibition capacity, high hemocompatibility and not altering the metabolism of monocytes and fibroblasts growing on them. Therefore, these novel hydrogels represent biomaterials with potential application in biomedical strategies such as wound healing dressings. [Display omitted] •The polyacrylate content regulates the polymerization rate, structure andphysicochemical properties of hydrogels.•A direct relationship among the polyacrylate concentration and mechanical, thermal improvement and degradation control is observed.•The presence of polyacrylate grants improved antibacterial capacity and hemocompatibility.•The biocompatibility of collagen is not altered in hydrogels that include 20 wt. % of polyacrylate.•These hydrogels represent biomaterials for potential application as chronic wound healing dressings.